Pemphigus vegetans Hallopeau with nail changes and no oral involvement - Tomanovic, Marija; Lalosevic, Jovan; Skiljevic, Dusan; Zivanovic, Dubravka (Medical Research, 2023)
Introduction: Pemphigus vegetans (PVeg) is the rarest form of autoimmune pemphigus. Lesions are primarily flexural and mucosal, although they may occur at any site. Oral involvement is common. Two subtypes are recognized- the Neumann type and the less common Hallopeau type. Patient review: We present a Hallopeau-type PVeg with no oral lesions and uncommon nail changes. In the follow-up period of ten years, she experienced several flares but no changes in the oral cavity.Conclusion: This case is interesting due to the disease’s rarity, atypic clinical presentation, and the association with multiple pregnancies as a possible precipitating factor.